From Mazahua to Nobles: The Case of the Villegas Chimal Family in the North of the Valley of Toluca, in the 16th-18th Centuries - Santiago Cortez, Felipe (Revista Complutense de Historia de América, 2022)
This article addresses how a Mazahua Indian by the name of Francisco de Villegas was able to adapt to the colonial system by allying himself with his encomendero namesake in order to obtain remarkable power based on economic resources throughout the Valley of Toluca. Since then, the Villegas Chimal family became the new Mazahua nobility and each of its descendants sustained wealth and political influence in two Indian towns during three centuries: Atlacomulco and San Miguel Temascalcingo.
Keywords: Family; Indian Chiefs; Mazahua; Toluca; 16th-18th Centuries